ANALISIS FRAUD DIAMOND DALAM DETERMINASI PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN DENGAN FAMILY OWNERSHIP SEBAGAI VARIABEL MODERASI - Devira Puri Ayu Melati; Dwi Jaya Kirana; Noegrahini Lastiningsih (Jurnal Ilmiah Manajemen Ubhara, 2020)
Abstract - The purpose of this research is to determine the influence of financial targets, ineffective monitoring, rationalization, and capability of fraud detection of financial statements. This research also uses family ownership as a moderation variable. The fraudulent financial reporting in this study were measured using earnings management. The population in this research is a banking company listed on the Indonesia Stock Exchange (IDX) for the period 2016-2018. The amount of samples is 123 samples for Model 1 and Model 2. The analytical methods used are multiple linear regression analyses, coesfisien determinations, simultan test (test F) and partial test (Test T) with application SPSS (Statistical Product and Service Solution) version 25th . The research result indicates that financial target, ineffective monitoring, rationalization, and capability have a significant influence on the detection of fraud financial statements and family ownership can moderate variable relationships Capability change of Directors on fraud detection of financial statements. Keywords: fraudulent financial reporting , fraud diamond, family ownership